MOFs@COFs composites: Advances, challenges, and multifunctional applications in emerging technologies - Khalil Ahmad; Muhammad Mateen Afzal Awan; Muhammad Kashif; Khizar Qureshi; Irfan Ahmad; Muhammad Altaf Nazir; Habib Ur Rehman Shah; Muhammad Ashfaq (Hybrid Advances)
MOFs and COFs are two remarkable classes of crystalline porous materials, boasting unique attributes such as remarkable surface area, customizable pore sizes, and a wide array of functionalities. In recent eras, the combination of these materials into MOFs@COFs composites has garnered substantial attention, owing to their potential applications across various domains. Thanks to the robust covalent bonds established between MOFs and COFs, these hybrid structures demonstrate exceptional applications in numerous fields like biosensors, water purification, energy storage, water splitting, and drug delivery. This meticulous review encapsulates the recent advances in synthesizing and characterizing MOFs@COFs composites, highlighting their exceptional characteristics and extensive applicability. We have discussed challenges and opportunities of this rapidly evolving field, inherent in designing and synthesizing pioneering MOFs@COFs composites, while elucidating their multifunctional roles in biosensing, adsorption, energy storage devices, gas separation technologies, water-splitting advancements, and drug delivery systems. Through an inclusive examination of the current state of the art, this review offers valuable insights into the future perspectives of this attractive research domain, illuminating new perspectives and directions for advancements and innovative inventions.